2022
DOI: 10.1016/j.pulmoe.2021.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Practice of tracheostomy in patients with acute respiratory failure related to COVID–19 – Insights from the PRoVENT–COVID study

Abstract: Objective Invasively ventilated patients with acute respiratory failure related to coronavirus disease 2019 (COVID–19) potentially benefit from tracheostomy. The aim of this study was to determine the practice of tracheostomy during the first wave of the pandemic in 2020 in the Netherlands, to ascertain whether timing of tracheostomy had an association with outcome, and to identify factors that had an association with timing. Methods Secondary analysis of the ‘PRactice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
(50 reference statements)
1
5
0
Order By: Relevance
“…Assessing our data from the first wave, we observed long ITTs of 18.64 ± 5.46 days in April 2020. Similar data can be observed in the Netherlands, for example, which suggest that tracheostomy was performed exceptionally late during the first wave of the pandemic from March to May 2020 in comparison to standard practice 41 . This observation may be explained by particular concerns of infection of healthcare providers when performing tracheostomy at the beginning of this pandemic which resulted in recommendations by many medical societies to delay this aerosol generating procedure 28 .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Assessing our data from the first wave, we observed long ITTs of 18.64 ± 5.46 days in April 2020. Similar data can be observed in the Netherlands, for example, which suggest that tracheostomy was performed exceptionally late during the first wave of the pandemic from March to May 2020 in comparison to standard practice 41 . This observation may be explained by particular concerns of infection of healthcare providers when performing tracheostomy at the beginning of this pandemic which resulted in recommendations by many medical societies to delay this aerosol generating procedure 28 .…”
Section: Discussionsupporting
confidence: 75%
“…With an increased mortality hazard ratio when performing tracheostomy at day 10 or earlier, early tracheostomy appears to worsen patient outcome in COVID-19. This is rather surprising, as we expected a benefit or at least non-inferiority of early tracheostomy for our patients, because studies in patients with or without COVID-19 infection scarcely indicated increased mortality in patients undergoing early tracheostomy 12 18 , 41 , 43 . Our data appear to indicate that delaying tracheostomy may in fact benefit our patients.…”
Section: Discussionmentioning
confidence: 80%
“…No RCTs were, however, available for this meta-analysis. Newly published both prospective [ 21 ] and retrospective [ 22 ] studies indicate that early tracheotomy implies fewer days of MV and shorter length of stay at the ICU. In accordance to the findings of the latter studies, a retrospective analysis of COVID-19 patients from the first wave of the pandemic performed at our department suggested early tracheotomy to be correlated with a shorter time on MV and, consequently, a shorter ICU stay [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there exist several protocols, universally accepted ones are lacking as well as RCTs on this critical issue 53 . Training in pulmonological techniques may help 54 .…”
Section: Tracheostomy and Decannulationmentioning
confidence: 99%